Effectiveness of Resilience Interventions on Psychosocial Outcomes for Persons With Neurocognitive Disorders: A Systematic Review and Meta-Analysis - Wang, Ying; Chi, Iris; Zhan, Yuning; Chen, Wenjang; Li, Tongtong (Frontiers in Psychiatry, 2021)
Background: Neurocognitive disorders, such as mild cognitive impairment (MCI), dementia, and Alzheimer's disease, not only harm people's cognitive function but also lead to negative emotions, poor quality of life (QOL), and unsatisfactory level of well-being. Resilience can be defined as a dynamic and amendable process, which maintains or improves life satisfaction and quick recovery from own dilemma. However, no meta-analysis of randomized controlled trials (RCTs) has thus far examined the effectiveness of resilience interventions among persons with neurocognitive disorders, and the results of RCTs were inconsistent. This systematic review aimed to assess the effectiveness of resilience interventions on psychosocial outcomes among persons with neurocognitive disorders. Methods: Nine electronic Chinese and English databases (the Cochrane Library, PsycINFO, Web of Science, PubMed, Medline, Eric, JSTOR, CNKI, and WANGFANG) were searched through April 2021. Only RCTs were included, and the quality of the included studies was assessed by the Cochrane “Risk of Bias” tool. Meta-analysis was carried out on psychosocial outcomes, and heterogeneity was investigated by subgroup and sensitivity analysis. RevMan 5.4 was used for meta-analysis. Results: Fourteen RCT studies were identified, representing a total of 2,442 participants with neurocognitive disorders. The risk of bias was high or unclear for most included studies in the domains of allocation concealment, blinding participants, and interventionists. Meta-analysis showed that heterogeneity was low or moderate. There were significant differences in favor of resilience interventions compared with control on the outcome of QOL, using the Quality of Life-Alzheimer Disease scale (QOL-AD) [I2 = 36%, standardized mean difference (SMD) = 0.14, 95% CI (0.02, 0.26), p = 0.02], and no significant differences on depression, using the Cornell Scale for Depression in Dementia (CSDD) [I2 = 41%, SMD = −0.14, 95% CI (−0.34, 0.05), p = 0.16], and neuropsychiatric symptoms using the Neuropsychiatric Inventory Questionnaire (NPI-Q) [I2 = 62%, SMD = −0.10, 95% CI (−0.37, −0.16), p ≤ 0.46]. Conclusions: Resilience interventions had a significant benefit on QOL but no significant benefit on depression and neuropsychiatric behavioral symptoms. More evidence is needed to answer questions about how to implement resilience interventions and how to evaluate their effectiveness.